Determinan Pengungkapan Islamic Social Reporting pada Bank Umum Syariah di Indonesia - Santoso, Arif Lukman; Dhiyaul-Haq, Zaki Murtadho (Jurnal Dinamika Akuntansi dan Bisnis, 2017)
This study aims to examine the determinants of the disclosure of Islamic Social Reporting (ISR) in the Indonesian Islamic banking industry. We used profitability, award and type of ownership as the determinants of Islamic Social Reporting. Profitability was proxied by the ROA, while the award was identified by a number of awards for CSR performance for one year, and the type of ownership was classified into four: government, family, foreign, and institutional ownership. The samples were Islamic banks (IB) in Indonesia, which had published annual report for the period of 2010-2014. The data were 53 annual reports of 12 IBs. Hypotheses were tested using multiple linear regression analysis. The results showed that profitability, award, and the type of ownership partially did not affect the disclosure of ISR. Further analysis was conducted to test the effect of all the variables on each theme in the index ISR. The results indicated that award had a positive effect on the social and corporate governance themes, and lastly type of ownership had an effect on the financial, product, human resources, social and governance themes.